Antibacterial and Antifungal Potential of Methanol Stem–Bark Extract of Mangifera Indica - Umaru, Kerenhappuch Isaac; Tansaba, Akafa Andes; Ugoeze, Egeonu Stephen; Nanmar, Chakfa; Umaru, Isaac John (Darul Yasin Al Sys, 2024)
Medicinal plants have served through the ages, as a constant source of medicaments for the exposure of variety of diseases. The history of herbal medicine is as old as human civilization. The plants are known to provide a rich source of botanical anthelmintic, antibacterial and insecticides. Mangifera indica (MI), popularly known as mango belong to the genus Mangifera and family Anacardiacea. The leaves, stem bark and roots are used as herbal medicines worldwide. In antibacterial analysis, higher growth inhibition rate was observed at 400 ug/ml for Klebsiella pneumonia with 20.55 + 1.26μg/mL indicating that the extract has effect at a higher concentration than when treated at a lower concentration. In blood glucose level analysis, administration of 100 mg/kg body weight of Mangifera indica stem bark methanolic extract showed reduced blood glucose level in day 14 with 5.11 ± 0.14a of treatment when compared to normal control.